What's new in Adobe AIR 3 - Labrecque, Joseph (Adobe developer library, 2012)
This book will present you with a full rundown of all the new features in the upcoming AIR 3.0 runtime. Along with each feature, if applicable, will be a demonstration of how to employ the new feature. There's also be a short introduction to AIR and a chapter dedicated to providing you with additional resources.